Integration of islamic education and digital literacy in twenty-first century learning - Miftahuddin Miftahuddin; Muhammad Rizki Perdana (Indonesian Institute for Counseling, Education and Theraphy, 2026)
The rapid development of digital technology has created new challenges and opportunities for Islamic education in the twenty-first century. Educational institutions are increasingly required to integrate digital literacy with Islamic values to support ethical and responsible technology use. This study aims to analyze the integration of Islamic education and digital literacy, identify implementation challenges, and explore learning development strategies relevant to contemporary educational contexts. The study employed a qualitative Narrative Literature Review (NLR) approach. Literature sources were collected from Google Scholar, Scopus, ScienceDirect, Springer, and Garuda databases using keywords related to Islamic education, digital literacy, and twenty-first century learning. Relevant journal articles, books, conference proceedings, and policy documents were selected based on their relevance, credibility, and alignment with the study objectives. The collected literature was examined through content analysis and qualitative descriptive analysis to identify recurring themes and conceptual patterns. The review revealed that the integration of Islamic education and digital literacy is consistently associated in the literature with the development of critical thinking, creativity, communication, collaboration, and ethical awareness in digital learning environments. The analysis also identified major implementation challenges, including limited teacher digital competence, unequal technological infrastructure, weak curriculum integration, ethical risks in digital media, and resistance to educational change. The findings highlight the importance of teacher development, curriculum transformation, technology-supported learning ecosystems, and multi-stakeholder collaboration in strengthening the integration of Islamic values and digital literacy within twenty-first century education.